Squamous cell carcinoma of scrotum mimicking as non-healing ulcer: a case report - T., Varadheswari; Priya B., Sathya; C., Vivekanand (International Surgery Journal, 2024)
Scrotal cancer is an extremely rare malignancy, with squamous cell carcinoma (SCC) being the most common histological subtype. Despite its rarity, the condition presents significant diagnostic and therapeutic challenges, particularly in cases of delayed presentation and atypical features such as abscess formation within the tumor. A 51-year-old male with diabetes presented with a three-year history of a non-healing ulcer on the scrotum. Clinical examination revealed a distinct ulcer with everted margins, necrotic tissue, and inguinal lymphadenopathy. Radiological investigations, including pelvic MRI and inguinal ultrasonography, confirmed scrotal wall thickening and enlarged lymph nodes bilaterally. The patient underwent wide local excision of the scrotal ulcer, left orchidectomy, and ilioinguinal lymph node dissection. The patient recovered without complications. Histopathological examination confirmed infiltrating moderately differentiated squamous cell carcinoma, staged as T2N1M0. The findings underscored the complexity of diagnosis and the necessity for a multidisciplinary treatment approach. This case highlights the diagnostic difficulties associated with scrotal SCC, particularly in the context of delayed presentation. Early detection and comprehensive treatment strategies, including surgical excision and lymph node dissection, are critical for improving patient outcomes in this rare malignancy.